A new species of understory palm of the genus Chamaedorea (Arecaceae: Arecoideae) from Costa Rica - Cascante-Marín, Alfredo; Muller, Fred (Phytotaxa, 2020)
Chamaedorea vanninii Cascante & Muller (Arecaceae, Chamaedoreeae) from the Central Pacific region of Costa Rica, Southern Central America, is described and illustrated. This new species is characterized by its orange ripe fruits with a conspicuous echinulate-medusoid epicarp. It is related to C. robertii which possesses black and smooth fruits. In addition, the androecium of staminate flowers of C. vanninii is composed of a single whorl of three stamens. This new species belongs to subgenus Chamaedoropsis and is provisionally considered as an endemic species and Critically Endangered (IUCN Red List criteria) because of its restricted geographic range and small population.